Development of integrated fertilizer management strategies in lentil for higher productivity in the south-western region of Bangladesh - Kobir, Md.Shahriar; Harun-Or-Rashid, Md.; Ahmed, Sharif (Ideas Spread, 2020)
Due to the lack of optimum fertilizer management in low organic matter content soil is one of the limiting factors to the lower yield and productivity of lentil in Bangladesh.To increase the yield and maintain the sustainability of lentil production in the highly intensive cropping areas of Bangladesh the development of integrated fertilizer management is urgent. An experiment was conducted at Regional Agricultural Research Station, Jashore, Bangladesh during the rabi season of 2018-2019 to develop an integrated fertilizer management strategies for lentil in low organic matter content soil. The experiment was laid out in a split plot design where different fertilizer management techniques were allocated in the main-plots and different varieties were allocated in the sub-plots. There were five fertilizer management (FM) techniques such as FM1- Vermicompost 1t ha-1+ (inorganic P:K:S @ 23:6:10 kg ha-1) + 2% DAP foliar spray, FM2- Vermicompost 1t ha-1+(inorganic P:K:S @ 24:6:10 kg ha-1)+ 1% DAP foliar spray, FM3- (inorganic N:P:K:S @ 20:40:20:10 kg ha-1) and no DAP foliar spray, FM4- Vermicompost 1t ha-1+ (inorganic P: K: S @ 25:6:10 kg ha-1) and no DAP foliar spray, FM5- control and there were three varieties such as V1-BARI Masur-6, V2-BARI Masur-7 and V3-BARI Masur-8. The highest plant height (cm), plant density at harvest, leaf chlorophyll index, grain yield and the lowest days to 50% flowering and Stemphyliumblight disease score was observed from the treatment combination FM1V3 (vermicompost 1t ha-1+ (inorganic P:K:S @ 23:6:10 kg ha-1) + 2% DAP foliar spray with lentil variety BARI Masur-8). The next best treatment combinations were FM1V2 (vermicompost 1t ha-1 + (inorganic P:K:S @ 23:6:10 kg ha-1) + 2% DAP foliar spray with lentil variety BARI Masur-7) and FM1V1 (vermicompost 1t ha-1 + (inorganic P:K:S @ 23:6:10 kg ha-1) + 2% DAP foliar spray with lentil variety BARI Masur-6), respectively. Integrated fertilizer management technique such as vermicompost 1t ha-1+ inorganic P:K:S @ 23:6:10 kg ha-1 + 2% DAP foliar spray with variety BARI Masur-8 may be recommended to farmers for sustainable lentil production.